PENGEMBANGAN BAHAN AJAR VIDEO PEMBELAJARAN MICROLEARNING MATERI SISTEM PENCERNAAN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Amalia, Reski; Ardhi Prabowo; Agung Tri Prasetya; Decky Avrilianda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop microlearning-based video teaching materials on the human digestive system for fifth-grade students at the UPTD SDN 257 Paojepe. The study used the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The validity of the teaching materials was measured through assessments by material experts and media experts, practicality was measured through teacher and student responses, and effectiveness was measured through learning outcome testing using pre- and post-tests. The results indicate that the developed microlearning video teaching materials meet the criteria of validity, practicality, and effectiveness in improving student learning outcomes.